2000
DOI: 10.1128/jb.182.11.3298-3301.2000
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the Caulobacter crescentus S-Layer Protein: Further Localization of the C-Terminal Secretion Signal and Its Use for Secretion of Recombinant Proteins

Abstract: The secretion signal of the Caulobacter crescentus S-layer protein (RsaA) was localized to the C-terminal 82 amino acids of the molecule. Protein yield studies showed that 336 or 242 C-terminal residues of RsaA mediated secretion of >50 mg of a cellulase passenger protein per liter to the culture fluids.The gram-negative bacterium Caulobacter crescentus possesses a paracrystalline protein surface (S) layer covering the outer membrane (24). The S-layer protein (RsaA) is secreted by a dedicated three-component A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Mutations (8) and truncations (9) in the RsaA extreme N terminus lead to an S-layer shedding phenotype. A species of smooth lipopolysaccharide (SLPS), whose O side chain is composed at least in part of N-acetylperosamine, is found on the outer membrane of C. crescentus (2).…”
mentioning
confidence: 99%
“…Mutations (8) and truncations (9) in the RsaA extreme N terminus lead to an S-layer shedding phenotype. A species of smooth lipopolysaccharide (SLPS), whose O side chain is composed at least in part of N-acetylperosamine, is found on the outer membrane of C. crescentus (2).…”
mentioning
confidence: 99%
“…All of these considerations have implications for the development of biotechnological applications based on the expression of foreign proteins using the Caulobacter S-layer protein. Indeed, we have exploited the S-layer secretion apparatus in order to express heterologous proteins as large as 600 aa in size (23) by fusing them to portions of RsaA containing the C-terminal secretion signal (5)(6)(7). The resulting protein products are secreted from C. crescentus at yields ranging up to 250 mg/liter (7).…”
mentioning
confidence: 99%
“…Prior work has shown that C. crescentus, a Gram-negative bacterium, has an S-layer subunit composed of a single highly expressed (27) protein (RsaA), secreted by a type I mechanism, such that there is no cleaved N-terminal signal leader but there is an uncleaved C-terminal secretion signal (4,11). Six RsaA monomers (12) form the characteristic hexagonal core with p6 symmetry seen by image analysis (47,48), and the 2D lattice is completed by hexagonal cores connected at junction points with p3 symmetry (Fig.…”
mentioning
confidence: 99%